Опыт разделения рода Tettigometra Latr. (Homoptera, Tettigometridae) на подроды - Емельянов, А.Ф. (Вестник зоологии, 1980)
Composition of the genus Tettigometra is revised. The genera Eurychila Sign, Mitricephalus Sign., Macrometrina Lindb. are considered as subgenera of Tettigo-Macrometrina are considered metra, the genera Brachyceps Kirk. and Micrometrina Sign. are considered as homonyms of the subgenus Tettigometra s. str. The new subgenera Metroplaca, Mimarada, Hystrigonia and Stirometra are described. A list of investigated species of each subge-nus from this genus and key of the subgenera are given.